ANALISIS PENGARUH VARIASI ARAH PENGELASAN HARDFACING TERHADAP KEKUATAN TARIK DAN STRUKTUR MIKRO PADA BAJA ASTM A36 - Awali, Jatmoko; Maulana, M. Arzil; Rohimsyah, Fikan Mubarok; Triana, Yunita (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
Welding is a metal joining process with filler or without filler. The welding method is also used to thicken the surface of the material or hardfacing. Hardfacing is a welding process with the aim of improving mechanical properties and is used on worn components by using SMAW welding, SMAW welding is used because it is relatively inexpensive and flexible. The purpose of this study was to determine the effect of hardfacing with SMAW welding direction variations on the tensile strength and microstructure of ASTM A36 steel material. The welding directions are horizontal, vertical and diagonal. This study used ASTM A 36 steel with a thickness of 5 mm. The welding electrode was E7018 with a diameter of 3.2 mm and a current of 130 A. After conducting this research, the highest average tensile strength value was found in the vertical direction, which was 474.74 N/mm2. The average value of the tensile strength in the diagonal direction is 446.715 N/mm2. The average horizontal tensile strength value is 420.785 N/mm2.